Frequency of health‐care utilization by adults who use illicit drugs: a systematic review and meta‐analysis. (10th February 2020) - Lewer, Dan; Freer, Joseph; King, Emma; Larney, Sarah; Degenhardt, Louisa; Tweed, Emily J.; Hope, Vivian D.; Harris, Magdalena; Millar, Tim; Hayward, Andrew; Ciccarone, Dan; Morley, Katherine I.
Abstract: Aims: To summarize evidence on the frequency and predictors of health‐care utilization among people who use illicit drugs. Design: Systematic search of MEDLINE, EMBASE and PsychINFO for observational studies reporting health‐care utilization published between 1 January 2000 and 3 December 2018. We conducted narrative synthesis and meta‐analysis following a registered protocol (identifier: CRD42017076525). Setting and participants: People who use heroin, powder cocaine, crack cocaine, methamphetamine, amphetamine, ecstasy/3, 4‐methyl​enedioxy​methamphetamine (MDMA), cannabis, hallucinogens or novel psychoactive substances; have a diagnosis of 'substance use disorder'; or use drug treatment services. Measurements: Primary outcomes were the cumulative incidence (risk) and rate of care episodes in three settings: primary care, hospital admissions (in‐patient) and emergency department (ED). Findings: Ninety‐two studies were included, 84% from North America and Australia. Most studies focused on people using heroin, methamphetamine or crack cocaine, or who had a diagnosis of drug dependence. We were able to conduct a meta‐analysis of rates across 25 studies reporting ED episodes and 25 reporting hospital admissions, finding pooled rates of 151 [95% confidence interval (CI) = 114–201] and 41 (95% CI = 30–57) per 100 person‐years, respectively; on average 4.8 and 7.1 times more often than the general population. Heterogeneity was very high and was not explained by drugs used, country of study, recruitment setting or demographic characteristics. Predictors of health‐care utilization were consistent across studies and included unstable housing, drug injection and mental health problems. Opioid substitution therapy was consistently associated with reduced ED presentation and hospital admission. There was minimal research on health‐care utilization by people using ecstasy/MDMA, powder cocaine, hallucinogens or novel psychoactive substances. Conclusions: People who use illicit drugs are admitted to emergency department or hospital several times more often than the general population.